CD137 Signaling Promotes Endothelial Apoptosis by Inhibiting Nrf2 Pathway, and Upregulating NF-κB Pathway - Tianxin Geng; Yang Yan; Yue Zhang; Liangjie Xu; Guangyao Zang; Jin Chuan Yan (Mediators of Inflammation)
Background. Endothelial dysfunction and apoptosis resulting from oxidative stress can lead to the development of atherosclerosis. Our group has previously showed that CD137 signaling contributes to the progression of atherosclerosis and the vulnerability of plaques. The aim of this study is to investigate the effects of CD137 signaling in atherosclerosis on endothelial cells (ECs) apoptosis and to explore the underlying mechanisms. Methods. Serum samples were collected from 11 patients with acute myocardial infarction and 4 controls. Peritoneal injection of agonist-CD137 recombinant protein in ApoE−/− mice was used to determine whether CD137 signaling can promote apoptosis in vivo, and human umbilical vein endothelial cells treated with agonist-CD137 recombinant protein, M5580 (a Nrf2 pathway agonist) and CAPE (a NF-κB pathway inhibitor) were used to explore the effect of Nrf2 and NF-κB pathway in CD137 signaling-induced ECs apoptosis in vitro. Results. ELISA showed that Bcl-2 in the serum of AMI patients was lower than that of the control group, while TNF-α and sCD137 were higher than that of the control group. Confocal microscopy and Western blot analysis showed that the nuclear translocation of Nrf2 in the agonist-CD137 group was significantly inhibited, and the expression of its downstream antioxidant enzymes was also decreased when compared with control. Immunofluorescence and Western blot results showed that the nuclear translocation of NF-κB in the agonist-CD137 group was enhanced, and ELISA results showed that the secretion of proinflammatory cytokines in the agonist-CD137 group was increased. Immunofluorescence results revealed that ROS production in the agonist-CD137 group was higher than that in control, M5580 (a Nrf2 pathway agonist) and CAPE (a NF-κB pathway inhibitor) groups. In vitro studies using HUVECs and in vivo studies using high-fat-fed ApoE−/− mice showed that the number of apoptotic endothelial cells was the highest in the agonist-CD137 group. By contrast, both M5580 and CAPE treatments were able to reduce CD137 induced ECs apoptosis. Conclusions. Our results showed that CD137 signaling promotes ECs apoptosis through prooxidative and proinflammatory mechanisms, mediated by Nrf2 and NF-κB pathways, respectively.